2009
DOI: 10.1210/er.2009-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondria in the Pathophysiology of Skeletal Muscle Insulin Resistance

Abstract: Multiple organs contribute to the development of peripheral insulin resistance, with the major contributors being skeletal muscle, liver, and adipose tissue. Because insulin resistance usually precedes the development of type 2 diabetes mellitus (T2DM) by many years, understanding the pathophysiology of insulin resistance should enable development of therapeutic strategies to prevent disease progression. Some subjects with mitochondrial genomic variants/defects and a subset of lean individuals with hereditary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
113
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 258 publications
5
113
0
Order By: Relevance
“…The impaired SKM insulin signaling is crucial for systemic insulin resistance and precedes the development of diabetes (DeFronzo & Tripathy 2009, Pagel-Langenickel et al 2010. However, our study showed that HFD exerts minor effects on Irs1 and Glut4 mRNA in SKM compared with the change in WAT, agreeing with a previous report (Anai et al 1999).…”
Section: Discussionsupporting
confidence: 92%
“…The impaired SKM insulin signaling is crucial for systemic insulin resistance and precedes the development of diabetes (DeFronzo & Tripathy 2009, Pagel-Langenickel et al 2010. However, our study showed that HFD exerts minor effects on Irs1 and Glut4 mRNA in SKM compared with the change in WAT, agreeing with a previous report (Anai et al 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Mitochondrial dysfunction was an important event in the development of T2D and insulin resistance in adult life (Pagel-Langenickel et al, 2010). It has been shown that maternal high-fat diet-induced changes in mitochondrial biogenesis in offspring are associated with decreased mitochondrial functions (Mohamed et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle composes the largest metabolic tissue in the body and is one of the key insulinresponsive organs (Lowell and Shulman, 2005). Mitochondrial dysfunction in skeletal muscle has been associated with metabolic diseases in human and animal models (Pagel-Langenickel et al, 2010). Likewise, decreased oxidative phosphorylation, antioxidative capacity and mitochondrial electron transport chain enzyme activities in the liver and skeletal muscle have been observed in the offspring subjected to maternal overnutrition and diabetes (Bruce et al, 2009;Zhang et al, 2011;Latouche et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent work has also shown that, in the context of redox or direct proteotoxic stressors, SIRT3 in its capacity to enhance excess reactive oxygen species biology has an inverse, albeit indirect, and ameliorative effect on the mitochondrial protein folding machinery (43). Our study nevertheless advances the understanding of a mechanism that may explain the paradoxical findings, where nutrient excess and caloric restriction have profound effects on mitochondrial homeostasis and quality control (44,45). Further investigations into the mechanisms underpinning acetylation on the mitochondrial folding and unfolded protein responses should advance our insight into why caloric load can have direct effects on mitochondrial biology (44).…”
Section: Discussionmentioning
confidence: 62%
“…Our study nevertheless advances the understanding of a mechanism that may explain the paradoxical findings, where nutrient excess and caloric restriction have profound effects on mitochondrial homeostasis and quality control (44,45). Further investigations into the mechanisms underpinning acetylation on the mitochondrial folding and unfolded protein responses should advance our insight into why caloric load can have direct effects on mitochondrial biology (44).…”
Section: Discussionmentioning
confidence: 75%